Fully-covered esophageal stent migration rates in benign and malignant disease: a multicenter retrospective study - Thomas, Samuel; Siddiqui, Ali A.; Taylor, Linda Jo; Parbhu, Sheeva; Cao, Christopher; Loren, David; Kowalski, Thomas; Adler, Douglas G. (Endoscopy International Open, 2019)
Background and study aims Stent migration is a common complication of fully-covered self-expanding metal stents (FCSEMS), but the rate of clinically relevant migration as defined by stent migration followed by reintervention via endoscopy for stent replacement is unknown. The goal of this study is to gain insight into the total migration rate and clinically relevant migration rate of different types of FCSEMS placed within benign and malignant strictures with specific attention paid to stent manufacturer, diameter, and length.Patients and methods Multicenter retrospective analysis of endoscopic data from patients with FCSEMS placed within benign or malignant strictures. FCSEMS used included a variety of sizes and manufacturers.Results A total of 369 patients were included, 161 of whom had benign strictures and 208 of whom had malignant strictures. The total migration rate and clinically relevant migration rate in benign strictures were 30 % and 17 %, respectively. For benign strictures, Wallflex stents had a clinically relevant migration rate of 15 %, compared to Endomaxx stents with 19 %, and Evolution stents with 25 % (P = 0.52). The total migration rate and clinically relevant migration rates in malignant strictures were 23 % and 14 %, respectively. Evolution stents had a significantly higher clinically relevant migration rate (29 %) than the Wallflex stents (7 %) and the endomaxx stents (12 %), P = 0.003.Conclusion This study is the largest to investigate migration rates for FCSEMS in benign and malignant strictures. Clinically relevant migration is a relatively common occurrence with all stent types studied and better anti-migration features are needed.